Power and regions in ancient states an Egyptian and Mesoamerican perspective - Feinman, Gary M. 1951- (Cambridge elements: Elements in ancient Egypt in context, 2022)
The aim of the Element is to provide a comprehensive comparison of the basic organization of power in Mesoamerica and Egypt. How power emerged and was exercised, how it reproduced itself, how social units (from households to cities) became integrated into political formation and how these articulations of power expanded and collapsed over time. The resilience of particular areas (Oaxaca, Middle Egypt), to the point that they preserved a highly distinctive cultural personality when they were included or not within states, may provide a useful guideline about the basics of integration, negotiation and autonomy in the organization of political formations